Efeito da alimentação artificial energética em colmeias de melipona interrupta fornecido através de alimentadores individuais externos na cidade de Santarém - Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This work aimed to evaluate the development of colonies of the species Melipona interrupta reared in rational boxes with and without artificial feeding during the rainy season in Santarém, Pará. The experiment was carried out in the Didactic Meliponary of Zootechnics at the Federal University of West Pará - UFOPA, between the months of April to June 2022. Four hives were used, 3 in the INPA model and 1 of the rustic type, divided into 2 treatments with 2 repetitions. The exchange of energy artificial food was done twice a week and the calf discs and honey pots were counted every 15 days depending on the weather. Treatment 1 and 3, with artificial feeding, treatment 2 and 4 without the energy syrup. The energy food offered comprised a solution composed of 50% honey in 50% water and lemon. Regarding the variables observed in the experiment, there was no difference in the number of brood discs and honey pots, but there was a higher weight of the hives after artificial feeding.
Keywords: Meliponicultura; Alimento energético; Manejo; CNPQ:: CIÊNCIAS AGRÁRIAS